ZNF577 Methylation Levels in Leukocytes From Women With Breast Cancer Is Modulated by Adiposity, Menopausal State, and the Mediterranean Diet - Lorenzo, Paula M.; Izquierdo, Andrea G.; Diaz-Lagares, Angel; Carreira, Marcos C.; Macias-Gonzalez, Manuel; Sandoval, Juan; Cueva, Juan; Lopez-Lopez, Rafael; Casanueva, Felipe F.; Crujeiras, Ana B. (Frontiers in Endocrinology, 2020)
The methylation levels of ZNF577 in breast tumors has been previously identified as a possible epigenetic mark of breast cancer associated with obesity. The aim of the current study was to investigate differences in methylation levels of ZNF577 depending on obesity, menopausal state and dietary pattern in blood leukocytes, a non-invasive sample. The methylation levels of ZNF577 of two CpG sites (CpGs) located in promoter and island previously identified as differentially methylated according to adiposity and menopausal state by 450k array (cg10635122, cg03562414) were evaluated by pyrosequencing in DNA from the blood leukocytes of breast cancer patients (n=90; n=64 (71.1%) overweight/obesity and n=26 (28.9%) normal-weight) and paired tumor tissue biopsies (n=8 breast cancer patients with obesity; n=3/5 premenopausal/postmenopausal women). Differences in methylation levels were evaluated at each CpGs individually and at the mean of the two evaluated CpGs. Adherence to the Mediterranean diet was evaluated using the MEDAS-validated questionnaire, and the consumption of food groups of interest was also evaluated using the recommended intakes of the Sociedad Española de Nutricion Comunitaria. The methylation levels of ZNF577 were correlated between paired leukocytes and breast tumor biopsies (r=0.62; p=0.001). Moreover, higher methylation was found in leukocytes from patients with obesity (p=0.002) and postmenopausal patients (p=0.022) than patients with normal-weight or premenopausal, respectively. After adjusting for the body mass index and age, higher levels of ZNF577 methylation were also found in women with greater adherence to the Mediterranean diet (p=0.017) or specific foods. Relevantly, the methylation levels of ZNF577 showed a good ability for fish consumption detection (area under the ROC curve (AUC)=0.72;p=0.016). In conclusion, the association between methylation of ZNF577 and adiposity, menopausal state, and adherence to the Mediterranean diet can be detected in the blood leukocytes. The results guarantee the need of performing further studies in longer longitudinal cohorts in order to elucidate the role of ZNF577 methylation in the association between breast cancer, adiposity and dietary patterns.